Digital gender divide and convergence in the European Union countries - María López Martínez; Olga García Luque; Myriam Rodríguez Pasquín (Economics: The Open-Access, Open-Assessment Journal, 2021)
The aim of this study is to examine the digital gender divide in the European Union (EU) countries by applying two widely used indicators: percentage of the population who has used the Internet in the last 3 months (ICT-USE indicator) and percentage of the population who has made an online purchase in the last 3 months (ICT-PURCHASE indicator). With these indicators, the digital gender gaps are shown in absolute and relative terms. In addition, the European convergence beta and sigma, between the years 2007 and 2019, is also analyzed. The results among European countries show that the ICT-USE indicator has a lower dispersion than the ICT-PURCHASE indicator; hence, in general, the digital gender divide or gap is usually lower when ICT-USE is used in comparison with ICT-PURCHASE. The highest values of the digital gender gap in the EU, regardless of the indicator used, are found in Croatia and Italy, reflecting an unfavorable position for women. Ireland is also in this group, but in its case, the results show an unfavorable position for men. Additionally, Cyprus does not register gender differences in either of the two indicators analyzed. Finally, the convergence between European countries is corroborated, both in the indicators analyzed and in the different gender digital gaps built.
Keywords: J16; O33; O52; 330; convergence; digital economy; digital gender divide; European Union; ICT indicators